Design in Motion: Introducing Science/Animation. - Banner, Olivia; Ostherr, Kirsten (Discourse: Journal for Theoretical Studies in Media & Culture)
The article focuses on scientific animations which include integration of computer-generated animation techniques with scientists' reliance on computer modeling as a means of conducting research. It states that digital animations come with their own epistemology which is called object-oriented (OO) programming whose programming differs from other forms of programming. It mentions that animations are assumed to be sufficient replacement for the visualization tools.